2012
DOI: 10.1097/sla.0b013e3182592c62
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Surgery for Non-Obese Type 2 Diabetes

Abstract: Duodenal-jejunal bypass improved insulin sensitivity and β-cell function and reduced glucose-insulinotropic polypeptide, leptin, and glucagon production. Hence, DJB resulted in better glycemic control and reduction in insulin requirement but DJB did not result in remission of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Moreover, no study showed an increase in adiponectin due to a given procedure not also possibly explained by weight loss. The only studies which did not show a change in adiponectin were one showing a decrease in adiponectin after medical weight loss (85) and a study of duodenal-jejunal bypass in which the surgical group did not show a significant change in fat mass or BMI (86). It thus seems most likely that adiponectin production is increased secondary to weight loss in all procedures, since it is increased by weight loss of any kind, including medical weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, no study showed an increase in adiponectin due to a given procedure not also possibly explained by weight loss. The only studies which did not show a change in adiponectin were one showing a decrease in adiponectin after medical weight loss (85) and a study of duodenal-jejunal bypass in which the surgical group did not show a significant change in fat mass or BMI (86). It thus seems most likely that adiponectin production is increased secondary to weight loss in all procedures, since it is increased by weight loss of any kind, including medical weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…The exception was an investigation of an experimental operation that replicates the proximal intestinal bypass of RYGB without affecting the stomach, i.e., duodenal-jejunal bypass surgery. It caused substantially greater glycemic control than did nonsurgical care, despite equal weight change in both groups, further demonstrating weight-independent antidiabetes effects of proximal intestinal bypass (33). As is commonly observed, the effects of surgery on blood pressure and plasma lipids were less impressive than those on glycemia.…”
Section: Evidence Regarding the Use Of Bariatric/metabolic Surgery Tomentioning
confidence: 96%
“…This procedure involves repositioning the intestinal tract without restriction or exclusion of the stomach. Although DJB does not elicit the same weight loss effects as RYGB or BPD, this procedure has been shown to produce glucoselowering effects in nonobese rodents (Rubino et al 2004), and in a small subset of nonobese or mild-obese humans with type 2 diabetes, independent of weight loss (Cohen et al 2007, Lee et al 2010, Geloneze et al 2012. Moreover, in Asia, a novel surgery similar to a BPD-DS has been developed that involves a DJB with VSG, and has demonstrated initial success in the treatment of diabetes (Kasama et al 2009.…”
Section: Bariatric Surgerymentioning
confidence: 99%